SYSTEMATIC REVIEW STUDY: THE USE OF DIGITAL REPOSITORY AS AN AUXILIARY PEDAGOGICAL TOOL IN TEACHING PRACTICE IN THE CONTEXT OF HOSPITAL AND HOME CLASSES - Almeida Rodrigues de Souza, Ivanise (Revista Gênero e Interdisciplinaridade, 2024)
The use of digital repository as an auxiliary pedagogical tool in teaching practice in the context of hospital and home classes has been the subject of study and research. This approach seeks to explore how technology can be used to support teaching and learning in situations where students are away from traditional school. Digital repository is an online platform that allows you to store, organize and share educational resources such as study materials, activities, videos and scientific articles. This tool can be especially useful in hospital and home class contexts, where students are facing health challenges or physical restrictions that make their physical presence impossible at school. The use of the digital repository can also facilitate communication between teachers and students, allowing the exchange of information, clarifying questions and feedbacks. This virtual interaction can help minimize students’ feeling of isolation in hospital and home contexts, promoting the connection to school and the construction of support relationships. However, it is important to note that the use of the digital repository as an auxiliary pedagogical tool does not replace the presence and support of teachers. It is still necessary to have qualified professionals who can guide students, plan appropriate activities and evaluate their progress.